2018
DOI: 10.1002/adfm.201800003
|View full text |Cite
|
Sign up to set email alerts
|

Walnut‐Like Multicore–Shell MnO Encapsulated Nitrogen‐Rich Carbon Nanocapsules as Anode Material for Long‐Cycling and Soft‐Packed Lithium‐Ion Batteries

Abstract: Metal oxide‐based nanomaterials are widely studied because of their high‐energy densities as anode materials in lithium‐ion batteries. However, the fast capacity degradation resulting from the large volume expansion upon lithiation hinders their practical application. In this work, the preparation of walnut‐like multicore–shell MnO encapsulated nitrogen‐rich carbon nanocapsules (MnO@NC) is reported via a facile and eco‐friendly process for long‐cycling Li‐ion batteries. In this hybrid structure, MnO nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
115
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(123 citation statements)
references
References 60 publications
3
115
1
Order By: Relevance
“…The total XPS spectrum of NVP@NC is shown in Figure a, and the characteristic peaks of Na, P, C, V, and O elements are all displayed. Figure b shows the C1s spectrum: The peaks at 284.3 and 284.7 eV are due to sp 2 graphitization and sp 3 diamond‐like carbon, respectively, and the other peaks at 285.5, 286.4, and 289.0 eV correspond to C–N, O–C–O, and C–O type carbon, respectively, indicating that N‐doping does exist in NVP@NC composite. Figure c is a high‐resolution spectrogram of P2 p , from which it can be observed that the peaks of approximately 133.3 and approximately 134.3 eV belonged to P2 p 1/2 and P2 p 3/2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The total XPS spectrum of NVP@NC is shown in Figure a, and the characteristic peaks of Na, P, C, V, and O elements are all displayed. Figure b shows the C1s spectrum: The peaks at 284.3 and 284.7 eV are due to sp 2 graphitization and sp 3 diamond‐like carbon, respectively, and the other peaks at 285.5, 286.4, and 289.0 eV correspond to C–N, O–C–O, and C–O type carbon, respectively, indicating that N‐doping does exist in NVP@NC composite. Figure c is a high‐resolution spectrogram of P2 p , from which it can be observed that the peaks of approximately 133.3 and approximately 134.3 eV belonged to P2 p 1/2 and P2 p 3/2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Doping MnO with Co could enhance the migration rate of carrier and offer abundant cationic conversion reactions for lithium storage, leading to improved reaction kinetics and reversible capacity ,. To the best of our knowledge, such outstanding rate capability and cycling stability particularly in the high rate are superior to most previously reported MnO and MnO‐based hybrids (Table S1) ,,,,,…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, extensive efforts have been devoted to exploring advanced anode materials with both high specific capacity and excellent rate capability to replace graphitic electrode . Different from the intercalation mechanism of graphite, transition‐metal oxides (TMOs) such as CoO x , FeO x , SnO 2 , and MnO x store lithium ions through conversion reaction during cycling, leading to high theoretical capacity of 500–1000 mA h g −1 . One of the most attractive TMO‐based electrodes is MnO because of its high theoretical capacity (755.6 mA h g −1 ), low cost, environmental friendliness, and high natural abundance of Mn element .…”
Section: Introductionmentioning
confidence: 99%
“…What's more, the PCMS@MnOÀ M electrode still keeps a high reversible capacity of 935 mAh g À 1 and a nearly 100 % CE after 100 cycles. [27,37,48,49] The unique pomegranate-like micro-nano structure of PCMS@MnOÀ M enables the ultrahigh capacity, which is higher than the theoretical capacity. The phenomenon could be accounted for the pseudocapacitive effect of PCMS@MnOÀ M during chargedischarge process.…”
Section: Resultsmentioning
confidence: 97%
“…[10,11,13,21] In order to speed up Li storage of MnO-based anode, rational nanoengineering to construct micro/nano structured MnO-based materials have been studied. [27] Among various micro/nano structure designs, pomegranate-like structure consisted of nanostructured building units as core and conductive carbon as shell has many underlying advantages in high performance LIBs anodes. [26] In another study, Zhu et al prepared walnut-like multicore-shell structure of ultrafine MnO nanoparticles encapsulated nitrogen rich carbon nanocapsules as an anode for LIBs, it delivered remarkable electrochemical performances including high reversible capability of 762 mAh g À 1 at 100 mA g À 1 and stable cycling ability with 624 mAh g À 1 after 1000 cycles at 1000 mA g À 1 .…”
Section: Introductionmentioning
confidence: 99%